2021
DOI: 10.15829/1560-4071-2021-4251
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and epigenetic factors regulating the expression and function of the vitamin D receptor in patients with coronary artery disease

Abstract: Coronary artery disease (CAD) remains the leading cause of death and disability in developed countries. Using traditional risk factors for CAD, it is possible to predict the likelihood of acute coronary events in no more than 50% of cases. Therefore, the study of influence of genetic and epigenetic factors on the development of CAD is extremely important. Research in recent years has shown that vitamin D deficiency is a new risk factor for atherosclerosis and immune inflammation. Vitamin D implements protectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Scientists have discovered more than 470 SNPs in the VDR gene, and thoroughly studied the role of four SNPs, rs2225870, rs1544410, rs7975232 and rs731236, in the pathogenesis of different diseases (cancer, diabetes, Parkinson’s disease, myocardial infarction and CAD) [ 52 , 53 , 54 , 55 ]. Studies have shown that genetic polymorphism in the VDR gene is associated with CAD risk in different populations.…”
Section: Discussionmentioning
confidence: 99%
“…Scientists have discovered more than 470 SNPs in the VDR gene, and thoroughly studied the role of four SNPs, rs2225870, rs1544410, rs7975232 and rs731236, in the pathogenesis of different diseases (cancer, diabetes, Parkinson’s disease, myocardial infarction and CAD) [ 52 , 53 , 54 , 55 ]. Studies have shown that genetic polymorphism in the VDR gene is associated with CAD risk in different populations.…”
Section: Discussionmentioning
confidence: 99%
“…VDR expression is differently correlated with inflammatory cytokines expression and miRNAs regulation, mainly miRNA-21, -214, and -125. A single nucleotide polymorphism of the VDR gene constitutes a risk factor for coronary artery disease [ 86 ]. In macrophages, which are essential immune cells during the vascular inflammatory response, upregulation of miRNA-155 is associated with LPS induced hyper-inflammatory process by the inhibition of suppressor of cytokine signaling 1 (SOCS1).…”
Section: Genetic and Epigenetic Regulation Of Inflammation By Vitamin Dmentioning
confidence: 99%